ANALISIS YURIDIS TERHADAP ISBAT NIKAH YANG AKAD NIKAHNYA OLEH WALI HAKIM (STUDI PENETAPAN PENGADILAN AGAMA NANGA PINOH, NOMOR:56//PDT.P/2020/PA.NGP) - Reja, Reja; Hasan, Muhammad; Hakimah, Nur (Institut Agama Islam Negeri (IAIN) Pontianak, 2022)
The purpose of the study is to find out: 1. How is the juridical analysis of the applicant's arguments in submitting the marriage isbat on a copy of the determination of the Nanga Pinoh Religious Court Number ; 6//Pdt.P/2020/PA.Ngp 2. How is the juridical analysis of the judge's legal considerations in marriage isbat on a copy of the determination of the Nanga Pinoh Religious Court Number ; 56/Pdt.P/2020/PA.Ngp. This research uses a qualitative normative juridical research method. Sources of data in this study usingsecondary data obtained from official documents, books related to the object of research, namely a copy of the determination of the religious court Number: 56/Pdt.p/2020/PA.Ngp research results in the form of reports, theses, and statutory regulations law. The technique used to collect data is document study. In technical data analysis, the researcher performs technical content analysis (content analysis). Content analysis is a systematic study of records or documents as sources of data. Based on the analysis conducted, the researcher concludes that in submitting the arguments of the applicant in submitting a marriage isbat, in marriage the applicant uses a guardian judge that is not in accordance with the regulations with the Director General of Community Guidance Number 1 of 2015andPMA Number 30 of 2005, and the reasons for the applicants submitting the marriage certificate to obtain a marriage certificate and for making the applicant's child birth certificate which is not in accordance with the Compilation of Islamic Law Article 7 paragraph 3. AndThe consideration of the Nanga Pinoh Religious Court judge in determining the marriage isbat at number 56/Pdt.P/2020/PA.Ngp did not pay attention to the facts revealed by the trial such asjudge's position, so that the panel of judges only considered from the sociological aspect, namely in order to create benefit without paying attention to the philosophical aspect, namely legal justice and the juridical aspect, namely legal certainty, so that it does not fulfill these three elements, then a determination will be not good.